PENGARUH CUSTOMER VALUE TERHADAP KEPUASAN NASABAH PADA PT. BANK TABUNGAN NEGARA (PERSERO), Tbk (STUDI KASUS CABANG PEMBANTU H. M. YAMIN MEDAN) - Dewi Budhihartini (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
PT.Bank National Savings (Persero), Tbk was originally commissioned by the Indonesian government to be the only bank that handles the distribution of the mortgage (Housing Loan) to the lower middle class society is through a simple home mortgage and mortgage the house is very simple. However, with the change in government policy Indonesia, where all the banks are allowed to distribute mortgages, Bank BTN shifting business focus so that Bank BTN had to face competition from other banking institutions to foster positive values to its customers. This study is based on the premise that the importance of customer satisfaction to improve corporate profitability variables mepengaruhi tehadap customer satisfaction adalahNilai customer (customer value) that is the perception of the value derived from the performance attributes of products (savings), which consists of the value of the performance attributes of the product (benefit from interest rates, the benefits of the transaction tool functions, function pemindahanbukuan, and multipurpose savings), the value of the service (speed of service, professionalism of the staff, comfort, information, interactive relationship, a gift) and corporate image.This study focused research on customer satisfaction savings god Batara by reason of savings is a type of savings is the most preferred by customers PT.Bank National Savings (Persero), Tbk Kacapem M.Yamin.Jenis this research using associative approach, the research data is primary data and secondary data. The study sample as many as 99 respondents. Data analysis using multiple linear regression test.From the regression equation known customer value consists of the value of money, performance value, emotional valuee positive and significant impact on customer satisfaction PT. State Savings Bank (Persero) either partially or simultaneously.